Pemanfaatan Konseling Kelompok Trait and Factor dalam Pemahaman Minat, Bakat, dan Kepribadian terhadap Ketepatan Pemilihan Program Kerja pada Siswa SMK - Nova Uswatun Hasanah; Veny Agustini Prianggita (Universitas Mathla'ul Anwar Banten, 2020)
THE USE OF TRAIT AND FACTOR GROUP COUNSELING IN UNDERSTANDING INTERESTS, TALENTS, AND PERSONALITY ON THE ACCURACY OF WORK PROGRAM SELECTION OF VOCATIONAL SCHOOL STUDENTS. Students at the SMK level are a strategic age in terms of maturing individual attitudes, so it is important to be able to understand and be able to make proper plans in considering and making job decisions. But in fact, there are still many students who still have difficulties because they do not know their interests, talents, potentials, and lack information. According to researchers, the trait and factor group counseling is felt to be very helpful for students to measure the level of basic intelligence, talents, interests, and personality of students as well as the continuation of work or study, to recognize the weaknesses and strengths of each psychological aspect of each student. The results and measurements indicate that the accuracy of students in choosing work programs before being given the trait and factor group counseling is included in the medium category. And after being given group counseling, the accuracy of choosing a work program was included in the high category.